An improved approach for studying oscillation of generalized Emden–Fowler neutral differential equation - Osama Moaaz; Elmetwally M. Elabbasy; Belgees Qaraad (Journal of Inequalities and Applications, 2020)
Abstract The purpose of this work is to study the oscillation criteria for generalized Emden–Fowler neutral differential equation. We establish new oscillation criteria using both the technique of comparison with first order delay equations and the technique of Riccati transformation. Our new criteria are interesting as they improve, simplify, and complement some results that have been published recently in the literature. Moreover, we present an illustrating example.